(untitled) - Mitchell, Barry S. (Edinburgh, 2009)
This book brings together high-quality illustrations and a concise text focused on essential features. It is ideal for modern medial undergraduate curricula where basic sciences emphasise the principal points of relevance to the students. The book will aslo be useful for other undergraduate sciences dealing with the structure and function of animals other than humans. It will be valuable to those requiring knowledge of histology at postgraduate level (in medicine or science). It should also show the potential for using histology to advance research into the structure and function of the body.
Keywords: Cell biology monographs,Nghiên cứu tế bào sinh học